MISCONCEPTIONS OF PROSPECTIVE MATHEMATICS TEACHER IN LINEAR EQUATIONS SYSTEM - Dini Kinati Fardah; Evangelista Lus Windyana Palupi (Universitas Muhammadiyah Tangerang, 2023)
Misconceptions are still a problem in learning mathematics. The causes are very diverse, ranging from the cognitive abilities of students who are not good at mathematics to the teacher who is the trigger for this misconception. The misconception diagnostic test benefits readers as a reference and pressure point in conveying certain concepts that are prone to misconceptions. This study aims to diagnose the occurrence of misconceptions and to analyze the types of misconceptions in 29 prospective mathematics teachers on the two-variable (SPLDV) and three-variable (SPLTV) linear purchasing system materials. A test to detect conceptual errors was given to these prospective teacher students to diagnose conceptual errors that occurred when they studied SPLDV in junior high school and SPLTV in high school before being given linear sales system material in Elementary Linear Algebra courses. The results show that there are still classificational, correlational, and theoretical misconceptions. Theoretical misconceptions that occur in students are related to the definition of misconceptions and related to the definition and types of SPL solutions. Classificational misconceptions occur when students classify examples and non-examples of a given linear sales system. Correlational misconceptions occur in students, namely students cannot connect a statement related to SPLDV with its graphical representation of the statement given, also students are not precise in compiling mathematical models of everyday problems given so the solutions obtained are incorrect.